Analysis of the role of PilA proteins in the cyanobacterium Synechocystis sp. PCC 6803. - Linhartová, Markéta (Jihočeská univerzita, 2009)
The PilA proteins are major components of pili fibres which are essential for motility in bacteria. This project was focused on the role of the PilA proteins in cyanobacteria, specifically in the alternative functions that are not directly related to motility. The major task of this project was also to develop a method for the purification of the PilA1 protein from Synechocystis under native conditions and to analyze purified PilA1 protein in detail.
Analysis of the role of PilA proteins in the cyanobacterium Synechocystis sp. PCC 6803.
Keywords: protein; purifikace; funkce; sinice; pili; motilita; metabolismus; protein; purification; function; cyanobacteria; pili; motility; metabolism